DEVELOPING SCIENTIFIC-BASED ELEMENTARY LINEAR ALGEBRA LEARNING MODULE WITH ISLAMIC NUANCE - Andi Ika Prasasti Abrar; Nurfadila Ainun; Lisnasari Andi Mattoliang; Fitriani Nur (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to develop a learning module for elementary linear algebra courses based on scientific approach with Islamic nuances that are valid, practical, and effective. This research is a Research & Development using the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The test subjects in this study were students of the Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar, semester 2 (two) class A of 2020. The instruments used were expert validation sheet, module implementation observation sheet, learning management observation sheet, student response questionnaire, lecturer response questionnaire, student activity observation sheet, and learning outcomes test. Based on the results of the study, it was found that (1) the results of module validation and all research instruments were valid; (2) the ability of the lecturer to manage learning is in the very good category, the implementation of the module is categorized as fully implemented, and the lecturer gives a very positive response regarding the use of the module so that the module developed is categorized as practical; (3) students’ learning outcomes showed that of the 35 students who took the learning outcomes test, the percentage of students’ learning completeness was 85.71%, students’ activity in learning was in the very good category, and students gave very positive responses to the use of the module so that the module developed categorized as effective. It can be concluded that the scientific-based elementary linear algebra module with Islamic nuances has met the valid, practical and effective criteria.